Environmental Information System of the Republic of Latvia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The Latvia Constitution (Satversme), the law “On environmental protection” and Aarhus convention on access to information, public participation in decision-making and access to justice in environmental matters are main legislative acts of the Republic of Latvia dealing with environmental information. State environmental information system in general provides data needed for decision making process done by state authorities. Residents and non-governmental organizations have access to environmental information as well. Unfortunately direct information exchange among authorities, institutions, organisations, enterprises and citizens sometimes is proceeding with difficulties. Inquiries done in the country before UN summit on Environment and development (Johannesburg, 2002) outlined dissatisfaction by public and many unsolved problems. The Environment ministry has developed the Environmental Communication and Education Strategy and Action Program. In foreseeable future the Environmental information and education centre will be established as well as a network based on regional environmental boards and self-government institutions.